Pengaruh Model Pembelajaran Role Playing terhadap Keaktifan Belajar Pendidikan Agama Kristen dan Budi Pekerti Siswa Kelas XI SMA Negeri 1 Sipoholon Tahun Pembelajaran 2024/2025 (Jurnal Pendidikan Agama dan Teologi, 2025)
The purpose of this research is to determine the significant positive influence of the role-playing learning model on the learning engagement of Christian Religious Education and Character Education among eleventh-grade students at SMA N 1 Sipoholon in the 2024/2025 academic year. The method used in this study is quantitative research, and the type of research is a pre-experimental design in the form of a "one group pretest-posttest." The population consists of all eleventh-grade students at SMA N 1 Sipoholon in the 2024/2025 academic year who are Protestant Christians, totaling 265 students across 8 classes, with a sample size of 30 students selected from class XI-C using purposive sampling technique. Data was collected using a closed positive questionnaire consisting of 30 items. The results of the data analysis indicate that there is a significant positive influence of the role-playing learning model on the learning engagement of Christian Religious Education and Character Education among eleventh-grade students at SMA N 1 Sipoholon in the 2024/2025 academic year. 1) Test requirements analysis: a) the test for the expected relationship is proven with a significant test resulting in thitung > ttabel (α=0.05; dk=n-1=29) which is 9.381 > 2.042 thus indicating a significant effect between variable X and variable Y. b) correlation test results in rxy = 0.845 > rtabel (α = 0.05; ik = 95%; n = 30) which is 0.361. c) regression determination coefficient test (r2) = 71.4%. 2) Effect test: regression equation test results in the regression equation Y = 73.40 + 0.15X. Therefore, H0 is rejected and Ha, which states that there is a positive and significant effect of the role-playing learning model on the learning activity of Christian Religious Education and Moral Education for XI grade students at SMA N 1 Sipoholon in the Academic Year 2024/2025, is accepted